PENGARUH PERBEDAAN ATRAKTOR TERHADAP HASIL TANGKAPAN JUVENIL LOBSTER DENGAN KORANG DI DESA SANGRAWAYAN, PALABUHANRATU (The Effect of Different Attractor Against Catch of Juvenile Lobster By Korang in Sangrawayan Village, Palabuhanratu) - Harits Adli Tegar Nevada; Sulaeman Martasuganda; Nimmi Zulbainarni; Iwan Dirwana (Marine Fisheries: Jurnal Teknologi dan Manajemen Perikanan Laut, 2016)
ABSTRACT This research has been done in Palabuhanratu bay, Indonesia. Juvenile lobster (Panulirus sp.) is the main target fish in this research. This research was used Fish Aggregating Devices with two different types of attractor. This research was aimed to known differences in the effectiveness of attractor that had been calculated used on Mann-Whitney Methode. Attractor which used for comparison were seaweed and palm leaf as a test and a seaweed as a control. Korang was a tool that used to gotten a data and put a attractor. The result of comparition show that a total of catches with seaweed and palm leaf more than seaweed. From the result concluded that seaweed and palm leaf more effective than seaweed.